Wood in office spaces: The impact of different wooden furniture on aesthetic evaluation - Zhu, Yiwei; Wang, Qiang; Zhao, Feng (Frontiers in Psychology, 2023)
In modern urban life, individuals are spending an increasing amount of time in the office. However, working in an uncomfortable office space for extended periods can affect the physical and mental health of employees. On this basis, it is particularly important for employees to build a comfortable and healthy office environment that is conducive to their work. The present study aimed to explore the use of wood in office furniture to build a comfortable and healthy work environment. The introduction of wood in office spaces can effectively relieve the mental fatigue of employees. Focusing on wooden office furniture, this study explores its influence on the aesthetic evaluation of wooden office spaces by manipulating the wood color and coverage of the wooden furniture placed in office spaces. Experimenting with these changes will optimize the application of wood in office spaces, improve employees’ physical and mental health, and enhance their productivity. The results show that wood color and coverage significantly impact the aesthetic evaluation of wooden office spaces. People exhibit higher aesthetic evaluations of light and medium wood-colored office spaces and prefer spaces with low wood coverage. Mental health problems in the workplace are prevalent worldwide. The findings of this study provide a reference for the use of wooden furniture to optimize workplaces. Reasonable use of wood in office furniture could improve the physical and mental health of employees, thus boosting the productivity of companies.